Clothing Communication of the Typical Costume of Han Nationality in Modern Times - Ding, Mengshu; Qistina Donna, Lee Abdullah; Salmiah, Abdul Hamid (2020)
The typical dress of modern Han nationality is a part of Chinese traditional culture. In ancient times, this kind of dress was popular among the public at that time. However, with the development of time and people's ideas, the typical dress of modern Han nationality has gradually disappeared in everyone's eyes. People put on modern clothing for social communication, which illustrates the traditional culture of modern Han nationality's typical dress. If this situation is not reversed, it will inevitably lead to the defects of Chinese culture. Therefore, in a modern society, we must adopt relevant methods to realize the effective dissemination of modern Han nationality's typical costume. This paper discusses the significance and characteristics of modern Han nationality's typical clothing communication by analysing the development status of the clothing communication, and then putting forward the main points of clothing communication, communication methods, and precautions.